Studi Eksegesis Yohanes 12: 44-50 Tentang Arti Dan Makna Firman Yang Menghakimi - Zebua, Eka Kurniawan; Telaumbanua , Peniel (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2025)
The interpretation of John 12:44-50 regarding "the word that judges" raises a theological paradox in understanding Jesus' soteriological mission. Previous exegetical studies have not explored the tension between salvific and judgmental aspects in Johannine theology. This research analyzes the theological meaning of "the word that judges" through historical-grammatical exegesis to reveal the soteriological dimension within the context of Jesus' mission. The methodology employs historical-grammatical exegesis with lexicographical analysis of the Greek text NA28, contextual hermeneutical approach, and comparison of parallel pericopes within the Johannine corpus. Lexicographical analysis demonstrates that κρίνω carries nuances of "separation" (separative) rather than "condemnation" (punitive). "The word that judges" functions as a natural consequence of rejection toward φῶς (light), not as the primary purpose of the incarnational mission. The literary context reveals John 12:44-50 as the climax of the light-darkness theme with soteriological emphasis. "The word that judges" refers to a revelatory function that exposes humanity's spiritual condition, not God's active judgment. These findings contribute to understanding Johannine soteriology and provide a hermeneutical framework for contemporary pastoral application.